Physical and chemical grain properties of new registered common bean cv. ‘Kantar-05’ - Ismail Ozturk; Mazhar Kara; Sezai Ercisli; Faik Kantar (Universiti Kebangsaan Malaysia, 2010)
Moisture-dependent physical grain properties of a new registered common bean cultivar ‘Kantar-05’ were determined. Some important chemical parameters of the grain were also investigated. The average length, width and thickness of the grain were 12.48, 7.92 and 5.00 mm at 7.82% db (dry basis) moisture content. The values of bulk density and true density of the grains decreased from 793.37 to 683.62 kg/m3 (P<0.01) and from 1269.37 to 1206.55 kg/m3 (P<0.05) with increasing moisture content. The coefficients of dynamic friction increased from 0.180 to 0.316, 0.173 to 0.276, and 0.226 to 0.331 on steel, plywood and wood friction surface, respectively with increasing moisture content. The force of rupture decreased from 121.88 to 68.93 N with increase in moisture content. Phosphorus, potassium, calcium, sodium and magnesium contents were 5020 ppm, 5576 ppm, 3562 ppm, 780 ppm and 372 ppm, respectively wb% (wet basis) at the initial moisture content. The antioxidant activity and phenolic content of the grains were found to be 56.62 % and 24.82 μg GAE/mg db., respectively at the initial moisture content.